Pengaruh kompetensi auditor eksternal dan teknik audit berbantuan komputer terhadap jasa audit e-commerce - Ananda Putri, Dhea Wahyu; Sari, Rida Perwita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Along with the increasing number of e-commerce businesses in Indonesia, the need for e-commerce audit services is possible. E-commerce audit services are services performed to assure interested parties regarding the level of security. This study aims to find out why e-commerce audit services are still poorly known in Indonesia, so it is necessary to know in advance how much impact the competence of external auditors and computer-assisted audit techniques (TABK) has on the need for e-commerce audit services. This quantitative research with a population of 97 external auditors who work in Public Accounting Firms spread across Indonesia. Sampling using snowball sampling. The analysis technique in this study uses Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this study external auditor competence and computer-assisted audit techniques have a significant and positive effect on e-commerce audit services.